Prenatal screening of gestation. Physiological changes in pregnancy. - Vizcarra Durán, Luis (2015)
The most notable changes that pregnancy causes maternal body, seen in the genital canal and, especially in the uterus grows to a remarkable extent, taking the end of gestation approximately 32 cm. long, 24 wide and 22 cm deep. This growth is mainly due to hypertrophy of the pre-existing muscle cells and, in part, to the formation of new cells in the early months of pregnancy. At the same time, it grows much the size of blood vessels, especially the veins, near the placental site becomes large spaces, placental venous sinuses. Also notable is the hypertrophy of 105 lymph vessels and nerves in the uterine wall.